Heatwave planning: community involvement in co-producing resilience. Issue 7 (2nd October 2016) - Fagan-Watson, Ben; Burchell, Kevin
Abstract : Drawing on a thematic analysis of relevant policy documents, an apparent disconnect is identified between two associated contemporary UK policy areas: planning for heatwaves and community resilience. Regional and national policy documents that plan for heatwaves in the UK tend to focus on institutional emergency responses and infrastructure development. In these documents, although communities are mentioned, they are understood as passive recipients of resilience that is provided by active institutions. Meanwhile, contemporary discussion about community resilience highlights the potential for involving communities in planning for and responding to emergencies (although the concept is also the subject of critique). To improve heatwave preparation, planning and response, more effort by central and local governments is required to articulate and realize greater participation by individuals, and voluntary and community sector groups.